Redefining Health: Implication for Value-Based Healthcare Reform - Putera, Ikhwanuliman (Cureus, 2017)
Health definition consists of three domains namely, physical, mental, and social health that should be prioritized in delivering healthcare. The emergence of chronic diseases in aging populations has been a barrier to the realization of a healthier society. The value-based healthcare concept seems in line with the true health objective: increasing value. Value is created from health outcomes which matter to patients relative to the cost of achieving those outcomes. The health outcomes should include all domains of health in a full cycle of care. To implement value-based healthcare, transformations need to be done by both health providers and patients: establishing true health outcomes, strengthening primary care, building integrated health systems, implementing appropriate health payment schemes that promote value and reduce moral hazards, enabling health information technology, and creating a policy that fits well with a community.